Can a Common Currency Induce Intra-Regional Trade? The South-East Asian (ASEAN) Perspective, - Kabir, S.; Salim, Ruhul (Taylor & Francis, 2016)
Recent literature strongly suggests that a common currency could be a potential long‐term currency arrangement for Association of Southeast Asian Nations (ASEAN). However, a high level of macroeconomic heterogeneity among these countries raises questions about the viability of managing a common monetary policy in the long run. In response to such currency management policy debate, this study analyzes the intra‐regional trade induction capability of a common currency for the ASEAN region. Using a gravity model of trade and an extended event study approach, the study finds that a common currency would induce intra‐ASEAN trade by 11–14 cents against every dollar of ASEAN gross domestic product. However, if the cost of managing regional macroeconomic harmonization is substantially high, a currency union for the ASEAN economy not be cost effective.